Fundamentals of Complex Analysis Engineering, Science and Mathematics - Saff, E. B., 1944- and Snider, Arthur David (Noida, India Pearson Education, 2015)
This book provides a comprehensive introduction to complex variable theory and its applications to current engineering problems. It is designed to make the fundamentals of the subject more easily accessible to students who have little inclination to wade through the rigors of the axiomatic approachrepresentations of C programs, processor architecture, program optimization, memory hierarchy, linking, exceptional control flow, virtual memory and memory management, system-level I/O, network programming, and concurrent programming. The coverage focuses on how these areas affect application and system programmers ... The book is based on Intel-compatible (IA32) machines executing C programs on Unix or related operating systems such as Linux. Some familiarity with C or C++ is assumed, although hints are included to help readers making the transition from Java to C
Include Index
Keywords: Mathematical analysis -- Functions of complex variables